PENGARUH PENGOLAHAN TANAH TERHADAP JUMLAH SIMPANAN BIJI GULMA DI DALAM TANAH PADA TANAH ALLUVIAL - Feri Pratama; Sarbino Sarbino; Rahmidayani Rahmidayani (Perkebunan dan Lahan Tropika, 2022)
This study aims to determine the effect of tillage on the amount of deposits of weed seeds in the soil on alluvial soil. Research conducted at the Faculty of Agriculture experimental field Tanjungpura in August to December 2014. Identification and data processing carried out at the Laboratory of Plant Pests Tanjungpura University . Research using observation method with weeds growing vegetation analysis after tillage. Observations were made after 1 times tillage , 2 times , 3 times and 4 times. Results of this study indicate that there are five species of weeds that have the highest amount of seed bank with a value of SDR above 10 % and is considered an important weed that is, Borreria alata, Cyrtococcum sp, Ageratum conyzoides, Ludwigia parennis and Phyllantus debilis. Based on the results of this study concluded that as many as 1 times tillage can reduce the weed seed bank  in the soil deposits if done before the weeds produce seeds.